Outcome of Transurethral Resection of the Prostate in Benign Prostatic Hyperplasia Patients with Urinary Retention and Small Prostate Volume Based on Urodynamic Finding - Budaya, Taufiq Nur; Daryanto, Besut (International Journal of Psychosocial Rehabilitation, 2020)
The gold standard of treatment in BPH patients with urinary retention is Transurethral resection of the prostate (TURP). This study evaluated the outcome of TURP in BPH patients and urinary retention with small prostate volumes (20-40cc). The 56 patients aged more than 50 years and clinically diagnosed with BPH and urinary retention with prostate volume 20 cc-40 cc were enrolled in this study. We compared all parameters (age, prostate volume, pre-operative urodynamic study, length of urinary retention prior to TURP, post-operative Qmax and PVR) according to the IPSS following TURP. Three-months following TURP, 28 (50%) patients have mild LUTS and 28 (50%) patients have moderate LUTS. Patients with mild LUTS following TURP had higher The detrusor-pressure during Qmax (PdetQmax), The detrusor-pressure during CCmax (PdetCCmax), preoperative Qmax, Bladder Outlet Obstruction Index (BOOI), Bladder Contractiity Index (BCI) and post-operative Qmax compared to patients who experienced moderate LUTS following TURP (p 0,000; p 0,001; p 0,001; p 0,000; p 0,000 and p 0,000 respectively). Patients with moderate LUTS following TURP had longer in length of urinary retention, had higher The maximum cystometric-capacity (Ccmax), post operative PVR, compared to patients who experienced mild LUTS following TURP (p 0,001; p 0,006 and p 0,000 respectively). No significant differences in age, prostate volume, pre-operative compliance, PVR and weight of resected prostate during TURP between two groups. In almost of all patients with moderate LUTS following TURP had abnormality in bladder contraction (46% with detrusor overactivity and 54% with detrusor underactivity).